Do Co-Workers? Wages Matter? : Theory and Evidence on Wage Secrecy, Wage Compression and Effort - Gary Charness; Peter Kuhn (Institute for the Study of Labor (IZA), 2004)
We study worker and firm behavior in an environment where worker effort could depend on co-workers? wages. Theoretically, we show that an increase in workers? ?concerns? with coworkers? wages should lead profit-maximizing firms to compress wages under quite general conditions. However, firms should be harmed by such concerns, and such concerns can justify paying equal wages to workers of unequal productivity only when those concerns are asymmetric (in the sense that only underpayment matters). Our laboratory experiments indicate that workers? effort choices are highly sensitive to their own wages, but largely unresponsive to co-workers? wages. Despite this, in apparent anticipation of a negative worker reaction, firms in our experiment were more likely to compress wages when wages became public information. Profits were not significantly reduced by a requirement to make wages public. Overall, our results seem to weaken the case that either wage secrecy or wage compression is a profit-maximizing policy in practice.
Keywords: C92; M52; M12; J33; 330; experiments; effort; social preferences; jealousy; wage compression; wage secrecy; Leistungsmotivation; Lohnstruktur; Neid; Geheimhaltung; Vergütungssystem; Experiment